A "submunition" dual-drug system based on smart hollow NaYF4/apoferritin nanocage for upconversion imaging. Issue 40 (5th April 2016) - Zhou, Jie; Chen, Shanshan; Sun, Chong; Du, Qiuzheng; Luo, Pei; Du, Bin; Yao, Hanchun
Abstract : Bifunctional nanomaterials based on doxorubicin (DOX)-loaded NaYF4 and verapamil (Vp)-loaded apoferritin–folic acid nanocage dual-drug system (DOX/NaYF4 -Vp/AFn-FA) were synthesized for in vivo upconversion imaging and enhanced chemotherapy in breast cancers. Abstract : Synergetic therapy has exhibited important potential for the treatment of cancers, especially for drug-resistant cancers. In this report, bifunctional nanomaterials based on doxorubicin (DOX)-loaded NaYF4 and verapamil (Vp)-loaded apoferritin nanocage dual-drug system (DOX/NaYF4 -Vp/AFn-FA) were synthesized for in vivo upconversion imaging and enhanced chemotherapy in breast cancers. Moreover, folic acid (FA) targeting promoted the cellular uptake, and accelerated the release of DOX in drug-sensitive MCF-7. This system is a multifunctional drug delivery system with significant tumor-targeting efficacy and is also the first time preparation of NaYF4 –AFn-FA. The dual-drug system enabled a temporal release of two drugs: Vp was released rapidly to inhibit the activity of P-gp and restore cell apoptotic signaling pathways, while DOX was released in a more sustained manner and highly accumulated in drug resistant cells to exert a therapeutic effect, due to the inactivation of P-gp by Vp. Toxicity assessment in vitro and in vivo revealed the good biocompatibility of the as-prepared DOX/NaYF4 -Vp/AFn-FA nanocomposites. In addition, NaYF4 –AFn-FA uptaken by cells and mouse by intravenous injection showed bright green emission without background noise under 980 nm infrared laser excitation. Thus, NaYF4 –AFn-FA has the potential for simultaneous targeted anti-cancer drug delivery or imaging, which suggested a new multi-mechanism pathway for tumor treatment.